lncRNA Gm16410 Mediates PM2.5-Induced Macrophage Activation via PI3K/AKT Pathway - Xu, Jingbin; Xu, Henggui; Ma, Kexin; Wang, Yue; Niu, Ben; Zhang, Li; Li, Fasheng (Frontiers in Cell and Developmental Biology, 2021)
PM2.5 refers to atmospheric particulate matters with a diameter of less than 2.5 µm. Deposit of PM2.5 in lung cells can cause oxidative stress, leading to changes in macrophage polarity, which can subsequently cause pulmonary inflammation. Long-chain non-coding RNA (lncRNA) is a class of transcripts that regulate biological processes through multiple mechanisms. However, the role of lncRNA in PM2.5-induced lung inflammation has not been established. In this study, the biological effects and associated mechanism of lncRNA in PM2.5-induced change in macrophage polarity were investigated. In addition, the lncRNA-mediated PM2.5-induced macrophage inflammation and lung inflammation-associated injury was also determined. Mice were chronic exposed to PM2.5 and changes in the expression of lncRNA in the lung were measured by lncRNA microarray. LncRNAs that showed significant changes in expression in response to PM2.5 were identified. LncRNA showing the biggest change was subjected to further analysis to determine its functional roles and mechanisms with respect to macrophage activation. The result showed that significant reduction in expression of one lncRNA, identified as lncGm16410, was observed in the lung of mice and RAW264.7 cells following exposure to PM2.5. LncGm16410 suppressed PM2.5-induced macrophage activation via the SRC protein-mediated PI3K/AKT signaling pathway. PM2.5 promoted lung inflammation by downregulating the expression of lncGm16410, enhancing the activation of macrophage. Thus, lncGm16410 might provide new insight into the prevention of PM2.5 injury.